2004
DOI: 10.1680/stbu.2004.157.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Ductility and deformability of fibre-reinforced polymer-strengthened reinforced concrete beams

Abstract: This paper discusses the definition of, and the distinction between, deformability and ductility of reinforced concrete (RC) beams that are strengthened by advanced composites. The study examines the suitability of a new, design-based method for the determination of deformability, as well as an energy-based process, which is found to be suitable for quantifying the ductility levels of fibre-reinforced polymer (FRP)-strengthened RC members. Ten FRP-strengthened RC beams and four slabs have been load-tested to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Tann et al 33 suggested utilizing the deformability index D df to describe the loaded FRP bar RC beams subjected to large deformations, however, are not necessarily highly ductile. Ddfgoodbreak=normalΔ0.95normalΔnormals. …”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Tann et al 33 suggested utilizing the deformability index D df to describe the loaded FRP bar RC beams subjected to large deformations, however, are not necessarily highly ductile. Ddfgoodbreak=normalΔ0.95normalΔnormals. …”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…(6) There is no general agreement on how much deformability is enough with respect to the available deformability indices. Further study is necessary to provide a scientific basis for determination of the requirement.…”
Section: Discussionmentioning
confidence: 99%
“…According to Grace et al [5], if the energy ratio is 75% or greater, then the beam will exhibit a ductile failure. As pointed out by Tann et al [6], the Grace model is actually a reversed form of the Naaman model. If the energy ratio of Grace et al is 75%, then E tot /E el would be 1/(1−0.75) = 4, and the deformability index as determined by Eq.…”
Section: Energy-based Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…Research by Barrera et al (2012) and Spadea et al (2001) used two or more methods. Several types of ductility methods have been demonstrated in previous studies (Tann et al, 2004;Ghallab, 2014;Zou, 2003;El Zareef and El Madawy, 2018;Oudah and El-Hacha, 2012). However, only a few common methods have been identified, and many previously used ductility methods remain unidentified.…”
Section: Introductionmentioning
confidence: 99%